Patient classification and hospital reimbursement for inguinal hernia repair: a comparison across 11 European countries - Serdén, L.; O’Reilly, J. (Hernia : the journal of hernias and abdominal wall surgery, 2014)
Purpose This comparative study examines the categorisation of patients undergoing surgical repair of inguinal hernia in the diagnosis-related group (DRG) systems of 11 European countries (Austria, England, Estonia, Finland, France, Germany, Ireland, the Netherlands, Poland, Spain and Sweden). Understanding the design and operation of DRG systems for this common surgical procedure is important, given their increasing use internationally for hospital reimbursement and performance measurement. Methods A common definition was used to identify inguinal hernia patients and the corresponding data were extracted from national databases. The analysis compared the variables and algorithms for classifying these patients to DRGs across the participating countries, as well as the number, composition and relative resource intensity of groups. An index case and six standardised vignettes were grouped using each country’s DRG system and the associated quasi-prices were calculated. Results The number of groups to which inguinal hernia patients are assigned is typically three or four, but ranges from two in Poland to ten in France. In most systems, categorising patients is contingent on procedure, principal and secondary diagnoses, and age, with treatment setting (day case/inpatient) being less common. Added to these, the French system also incorporates length of stay and whether the patient died. More resource intensive DRGs generally contained patients who were older, treated as inpatients, did not die, had (more severe) complications and/or co-morbidities, and/or underwent laparoscopic repair. There are cross-country disparities in day case rates and the use of laparoscopic repairs. Conclusions The categorisation of inguinal hernia patients varies across the 11 European DRG systems under study. By highlighting the main differences across these systems, this comparative analysis allows the relevant decision makers to assess the adequacy and specificity of their own DRG systems.